PENGEMBANGAN PRAKTIKUM MICROSCALE UNTUK MENGANALISIS PEMAHAMAN PRINSIP GREEN CHEMISTRY - Allanas, Edith; Suryani, Elma; Affriliani, Putri Nur (Jurnal Riset Pendidikan Kimia (JRPK), 2024)
This study aims to analyze students’ understanding of the green chemistry of principles through implementing the microscale practicum with a modified-free inquiry learning model in acid-base solution material. Microscale practicum with inquiry learning model is applied to help students understand the green chemistry principles that are expected to be understood during the learning process. This study involved thirty six students in XI MIPA A Senior High School in Jakarta, 2022/2023 academic year. The qualitative method was employed to reveal the understanding of students' green chemistry principles  through multiple data collection of open-ended questions tests of understanding green chemistry principles, classroom observation, reflective journals, and semi-structured interviews. The study demonstrated that students' understanding of green chemistry principles increased with the implementation of microscale practicum with a modified-free inquiry learning model on acid-base solution materials. The concepts that students understand well are the principle of green chemistry in general, the principle of "Prevention", the principle of "Reducing Hazardous Chemicals", the principle of " ‘Design of Safe Chemicals", the design of "Safe Solvents", the principle of " Renewable Substance", and the principle of " Safer Chemistry to Prevent Accidents" in green chemistry. Thus, microscale practicum  with a modified-free inquiry learning model can help students understand the principles of green chemistry.